Extra Nodal Lymphoma, An Epidemiological and Histomorphological Trend of Primary Extra Nodal Lymphoma in India with Comparative Review of Articles - Vijaywargi, Sonali; Jamil, Syeda Firdos; Bandil, Supriya; Faujdar, Mansi; Gupta, Shubha (Annals of Pathology and Laboratory Medicine, 2022)
Background: Geographically there is considerable variation exists in epidemiology of extra nodal lymphomas. Aim: The aim was to study the epidemiological and histomorphological trends of Primary Extra Nodal Lymphoma (P-ENL) in India. Material &Methods: The biopsy materials from seventy patients with P-ENL (46 male, 24 female, M: F= 1.92:1), diagnosed over a period of two year (2014-2016), were analyzed and pathologically subclassified according to the 2008 World Health Organization (WHO) classification criteria. Results: Maximum incidence of P-ENL including both sexes was seen in age group 41-60 years. P-ENL constituted 23.72% and secondary extra nodal lymphomas constituted 6.7% of all lymphomas. 98.5% cases of P-ENL were Non-Hodgkin’s Lymphomas and 1.4% cases were Hodgkin’s lymphoma. The most common site involved by P-ENL was gastrointestinal tract 48.57%, followed by nasopharynx 12.8%, testis 8.4% and salivary gland 7.1%. DLBCL was the commonest lymphoma (72.8%) at all extranodal sites. B-cell phenotype predominated being 94.3% cases, followed by T-cell phenotype being 5.7% cases of P-ENL. Conclusions Gastrointestinal tract was the most common site involved by P-ENL followed by nasopharynx. Diffuse large B-cell lymphoma (DLBCL) was the most common subtype followed by marginal zone lymphoma. Majority of P-ENL cases were seen in immunocompetent hosts having a favorable prognosis.